2009
DOI: 10.1007/s00431-009-1005-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bariatric surgery: adverse outcomes in neonates

Abstract: These reports indicate that careful nutritional follow-up during pregnancy after obesity surgery is mandatory, because nutritional deficiencies such as vitamin K deficiency can lead to life-threatening bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…The most common nutritional deficiencies after RYGBP are of protein, iron, calcium, and vitamins B12, D, and folic acid [31,43], which all could have an impact on pregnancy. An increased risk of anemia has been reported during pregnancy after RYGB [43,44], and five cases of neonatal intracranial bleeding, all possibly related to vitamin K deficiency, have been reported following maternal bariatric surgery [45]. In two studies, the incidence of neural tube defects after RYGBP was higher than expected [46,47].…”
Section: Discussionmentioning
confidence: 98%
“…The most common nutritional deficiencies after RYGBP are of protein, iron, calcium, and vitamins B12, D, and folic acid [31,43], which all could have an impact on pregnancy. An increased risk of anemia has been reported during pregnancy after RYGB [43,44], and five cases of neonatal intracranial bleeding, all possibly related to vitamin K deficiency, have been reported following maternal bariatric surgery [45]. In two studies, the incidence of neural tube defects after RYGBP was higher than expected [46,47].…”
Section: Discussionmentioning
confidence: 98%
“…Obesity is associated with an increased risk of obstetric complications, such as gestational diabetes, pre-eclampsia, eclampsia, macrosomia, and fetal growth restriction [2,3]. Therefore, in view of the substantial increase in the prevalence of obesity among women of child-bearing age, a rise in the frequency of adverse maternal and fetal outcomes should be expected [4].…”
Section: Introductionmentioning
confidence: 98%
“…Women who have malabsorptive procedures might have deficiencies in iron, vitamin B12, or fat-soluble vitamins. Electrolyte abnormalities can result if recommended supplements are not taken or if the length of remaining small bowel is inadequate [16]. The National Institute for Health and Clinical Evidence concluded that; Surgery remains more effective than a non-surgical approach for people who are obese and weight loss after surgery has the potential to confer enormous health benefit for mother and child in the longer term (measured up to 10 years after surgery) [17].…”
Section: Discussionmentioning
confidence: 99%